Utilization Of Liquid Winprob Fermented Corn Ash With Various Time Durations For In Vitro Analysis Digestibility - Warisman; Siregar, Dini Julia Sari (International Forum of Researchers and Lecturers, 2024)
The purpose of this study is to determine the efficiency of corn ash fermented with Winprob for various durations on dry matter digestibility, organic matter digestibility, and crude fiber digestibility in vitro. The hypothesis proposed is that the addition of Winprob probiotics in corn ash fermentation at different times can improve the digestibility of dry matter, digestibility of organic matter, and digestibility of crude fiber. The research design used was a non-factorial completely randomized design (RAL) with four treatments and five replications. The treatments were studied as follows: P0 (control/corn ash without fermentation); P1 (corn ash fermented with Winprob for seven days); P2 (corn ash fermented with Winprob for 14 days); and P3 (corn ash fermented with Winprob for 21 days). The observed parameters include dry matter digestibility, organic matter digestibility, and crude fiber digestibility in livestock in vitro. The results showed that the treatment had a significant effect on the digestibility parameters of dry matter and the digestibility of coarse fiber and the digestibility of organic matter showed a significant influence (P>0.05).